Significant aspects of carbon capture and storage – A review - Raza, A.; Gholami, Raoof; Rezaee, M. Reza; Rasouli, V.; Rabiei, M. (2019)
Excessive emission of greenhouse gases into the atmosphere has resulted in a progressive climate change and global warming in the past decades. There have been many approaches developed to reduce the emission of Carbon Dioxide (CO2) into the atmosphere, among which Carbon Capture and Storage (CCS) techniques has been recognized as the most promising method. This paper provides a deeper insight about the CCS technology where CO2 is captured and stored in deep geological formations for stabilization of the earth's temperature. Principles of capturing and storage for a long-term sequestration are also discussed together with the processes, mechanisms and interactions induced by supercritical CO2 upon injection into subsurface geological sites.